2021
DOI: 10.1017/pan.2021.29
|View full text |Cite
|
Sign up to set email alerts
|

How Populist are Parties? Measuring Degrees of Populism in Party Manifestos Using Supervised Machine Learning

Abstract: One of the main challenges in comparative studies on populism concerns its temporal and spatial measurements within and between a large number of parties and countries. Textual analysis has proved useful for these purposes, and automated methods can further improve research in this direction. Here, we propose a method to derive a score of parties’ levels of populism using supervised machine learning to perform textual analysis on national manifestos. We illustrate the advantages of our approach, which allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
(90 reference statements)
0
21
0
Order By: Relevance
“…In supervised machine learning, still scarcely applied to measure aspects of populism (see Di Cocco and Monechi, 2022), the researcher in contrast 'trains' an algorithm, simulating coders' activity (for more information on this 'training', see appendix table C) 13 . In order to train the algorithm, we derived emotional scores per sentence using a Random Forest (RF) classification algorithm (Breiman, 2001) 14 , adopting a bag-of-words approach after text pre-processing.…”
Section: Methods and Sourcesmentioning
confidence: 99%
“…In supervised machine learning, still scarcely applied to measure aspects of populism (see Di Cocco and Monechi, 2022), the researcher in contrast 'trains' an algorithm, simulating coders' activity (for more information on this 'training', see appendix table C) 13 . In order to train the algorithm, we derived emotional scores per sentence using a Random Forest (RF) classification algorithm (Breiman, 2001) 14 , adopting a bag-of-words approach after text pre-processing.…”
Section: Methods and Sourcesmentioning
confidence: 99%
“…Lastly, we have shown that the fine-tuned models are competitive in terms of training time and inference time. Future research could explore the broader application of pretrained language models, alongside cross-domain classifiers, to other research questions, such as populism prediction (Cocco and Monechi 2022), sentiment and stance analysis (Bestvater and Monroe 2022), and party position analysis (Herrmann and Döring 2021), as well as the optimization of pretrained language models in training and inference.…”
Section: Training and Inference Timementioning
confidence: 99%
“…As attention to populist parties has grown, so too has the methodological work on identifying populism in text, including in party manifestos (Rooduijn and A key challenge has been to identify populism in short text, such as a sentence or a paragraph, in order to estimate the degree or amount of populism in a document. Given that no dataset exists that labels populist speech at the sentence level, recent work has proposed training sentence-level supervised classifiers to identify populism using manifesto-level labels (Di Cocco and Monechi 2021). This approach has been criticized, for, among other things, for relying on document-level labels to train a sentence-level classifier when most sentences in a populist party's manifesto will not be recognizably populist (Jankowski and Huber 2023).…”
Section: Application 3: Synthetic Data For Zero-shot Classifierstrain...mentioning
confidence: 99%